General Markers of Conscious Visual Perception and Their Timing - Rutiku, Renate; Aru, Jaan; Bachmann, Talis (Frontiers in Human Neuroscience, 2016)
Previous studies have observed different onset times for the neural markers of conscious perception. This variability could be attributed to procedural differences between studies. Here we show that the onset times for the markers of conscious visual perception can strongly vary even within a single study. A heterogeneous stimulus set was presented at threshold contrast. Trials with and without conscious perception were contrasted on 100 balanced subsets of the data. Importantly, the 100 subsets with heterogeneous stimuli did not differ in stimulus content, but only with regard to specific trials used. This approach enabled us to study general markers of conscious visual perception independent of stimulus content, characterize their onset and its variability within one study. N200 and P300 were the two reliable markers of conscious visual perception common to all perceived stimuli and absent for all non-perceived stimuli. The estimated mean onset latency for both markers was shortly after 200 ms. However, the onset latency of these markers was associated with considerable variability depending on which subsets of the data were considered. We show that it is first and foremost the amplitude fluctuation in the condition without conscious perception that explains the observed variability in onset latencies of the markers of conscious visual perception.